2000
DOI: 10.1101/lm.34100
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Plasticity in Hippocampal CA1 Neurons of Mice Lacking Type 1 Inositol-1,4,5-Trisphosphate Receptors

Abstract: In hippocampal CA1 neurons of wild-type mice, delivery of a standard tetanus (100 pulses at 100 Hz) or a train of low-frequency stimuli (LFS; 1000 pulses at 1 Hz) to a naive input pathway induces, respectively, long-term potentiation (LTP) or long-term depression (LTD) of responses, and delivery of LFS 60 min after tetanus results in reversal of LTP (depotentiation, DP), while LFS applied 60 min before tetanus suppresses LTP induction (LTP suppression). To evaluate the role of the type 1 inositol-1,4,5-trispho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 42 publications
3
66
1
Order By: Relevance
“…The fact that in the hippocampus BDNF/TrkB-mediated CA3-CA1 synaptic plasticity seems to be completely accomplished by the PLC␥ pathway is reminiscent of observations at the neuromuscular junction, where NT3-mediated synaptic potentiation is solely dependent on TrkC activated PLC␥ and IP 3 production (Yang et al, 2001). Not in line to these and our data are observations in which IP 3 R type I KO mice show a deficient longterm depression in the cerebellum (Inoue et al, 1998) and normal LTP in the hippocampus (Fujii et al, 2000). This difference could be because of the different stimulus protocol (a weak tetanus was used), the targeting of only IP 3 R type I, and the use of rather young mice before weaning.…”
Section: Discussioncontrasting
confidence: 41%
“…The fact that in the hippocampus BDNF/TrkB-mediated CA3-CA1 synaptic plasticity seems to be completely accomplished by the PLC␥ pathway is reminiscent of observations at the neuromuscular junction, where NT3-mediated synaptic potentiation is solely dependent on TrkC activated PLC␥ and IP 3 production (Yang et al, 2001). Not in line to these and our data are observations in which IP 3 R type I KO mice show a deficient longterm depression in the cerebellum (Inoue et al, 1998) and normal LTP in the hippocampus (Fujii et al, 2000). This difference could be because of the different stimulus protocol (a weak tetanus was used), the targeting of only IP 3 R type I, and the use of rather young mice before weaning.…”
Section: Discussioncontrasting
confidence: 41%
“…The functional roles of neuronal Ca 2ϩ stores are becoming increasingly recognized and include modulation of membrane excitability (Davies et al, 1996;Stutzmann et al, 2003), synaptic activity and plasticity (Fujii et al, 2000;Nakamura et al, 2000), and gene transcription (Mellstrom and Naranjo, 2001). However, to gain a better understanding of intracellular Ca 2ϩ signaling disruptions in neuropathology, we attempted to parse the IP 3 R and RyR components to identify interactions between these channels, as well as compartmentalize specific functions ascribed to each.…”
Section: Involvement Of Ryr In Ip 3 -Mediated Signaling In Neuronal Pmentioning
confidence: 99%
“…Our previous studies on hippocampal CA1 neurons in IP 3 R1-lacking mice demonstrated that the induction of LTP by a short tetanus of 10 pulses at 100 Hz or by a standard tetanus of 100 pulses at 100 Hz is facilitated in these mice (Fujii et al 2000b;Nagase et al 2003). Hippocampal CA1 neurons contain high levels of the type 3 RyR (RyR 3 ), but little type 1 or type 2 RyR (Furuichi et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Hulme et al (2012) showed that delivery of two trains of priming HFS (10, 20, 50, or 100 Hz, 10-min interval) to CA1 synaptic inputs reduces the level of LTP induced by a subsequent two trains of HFS (100 Hz, 1-sec trains with a 30-sec interval) and that this effect is attenuated when the HFS are delivered in the presence of an IP 3 R inhibitor. In addition, we ourselves demonstrated that the suppression of LTP induction by a preconditioning LFS (1000 pulses at 1 Hz) given 60 min before an HFS of 100 pulses at 100 Hz is attenuated in hippocampal CA1 neurons in IP 3 R1-deficient mice (Fujii et al 2000b). Recently, we showed that coactivation of NMDARs and IP 3 Rs during a preconditioning LFS results in an increase in the postsynaptic [Ca 2+ ] i in hippocampal CA1 neurons and in the dephosphorylation of synaptic proteins, leading to suppression of subsequent LTP induction (Yamazaki et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation